Analisis Kadar Logam Fe pada Air Sungai Emas Kampar sesuai SNI 6989-84:2019 - Dzakma Putri Alsa; Budhi Oktavia (MASALIQ, 2025)
This study is motivated by the critical importance of monitoring river water quality, particularly concerning heavy metal content such as iron (Fe), which poses potential risks to both human health and the environment. The objective of this research is to analyze the concentration of Fe in the water of the Kampar River using the Atomic Absorption Spectrophotometry (AAS) method. Water samples were collected from the Kampar River and subjected to a digestion process prior to measurement using AAS at a wavelength of 248.3 nm. The measurement results produced a calibration curve with a coefficient of determination (R²) of 0.9997, indicating a very strong linear relationship between concentration and absorbance. The analysis revealed that Fe concentrations in the samples ranged from 0.194 to 0.489 mg/L. While some samples exceeded the 0.3 mg/L threshold established by Government Regulation No. 82 of 2001 for Class II water quality, most remained within the permissible range. These findings demonstrate that the AAS method offers high sensitivity and accuracy in detecting Fe content in river water and can serve as a reliable tool for routine water quality monitoring.